Comparison of simulated gastric digestion behaviour of commercial infant formulae made with cow, goat and sheep milk : a thesis presented in partial fulfilment of the requirements for the degree of Master of Food Technology, Massey University, Manawatu, New Zealand - Song, Xuan (Massey University, 2022)
Infant formula is used as a supplement or substitutes to provide primary nutrition for infant growth and development when breastfeeding is not available. The different protein compositions from different animal milk and the process such as heat treatment during infant formula manufacture could impact protein digestion. This study compared the effects of protein composition and heat treatment on simulated gastric digestion behaviour of commercial infant formulae made with cow, goat, and sheep milk using an infant human gastric simulator (IHGS). Cow infant formula (CIF), goat infant formula (GIF) and sheep infant formula (SIF) were investigated in the present study. The results of the SDS-PAGE analysis indicated that the protein compositions, especially the casein compositions in three infant formulae were different. During the simulated dynamic gastric digestion, GIF chyme had an earlier initial aggregate compared to CIF and SIF, and the microstructures of GIF chyme showed fragmented and porous structures. On the contrary, CIF chyme formed dense protein networks that trapped oil droplets, whereas SIF chyme exhibited the structure of smooth oil droplets surrounded by fewer protein networks. The different aggregation behaviour and aggregate structures of three infant formula chyme could be related to the different protein compositions, especially the different casein compositions. Furthermore, the open friable structure of GIF aggregates could lead to pepsin being easier to access and hydrolyse protein. This is supported by the results of the SDS-PAGE pattern of emptied digesta obtain from CIF, GIF and SIF. However, the pH, particle size, protein, and fat contents of three infant formulae’s empty digesta only showed the difference at the late stage of the digestion. This indicated that the impact of different protein compositions of three infant formula on emptied digesta was subtle. To compare with unheated samples during gastric digestion, heated (90°C for 5 mins) CIF and GIF chyme showed a loose and fragmented structure. This could be attributed to the high temperature-induced denatured whey protein associated with the casein micelles by disulphide bonds and with other unfolded denatured whey proteins at the early stage of digestion. The result was in a line with the observations of protein hydrolysis of emptied digesta obtained from heated and unheated infant formulae. For heated samples of three infant formulae, both casein and whey protein were gradually hydrolysed by pepsin from the early stage of digestion. However, caseins of unheated samples were not hydrolysed until 100 min of digestion when the pH dropped to ~4.6. This suggested the hydrolysis rate was different between unheated and heated samples. Overall, the different protein compositions of infant formulae made with cow, goat and sheep milk affect the formation of structured coagulum. The initial coagulation times and the aggregate structures were affected by the protein compositions, especially the composition of casein, and the heat treatment. These different aggregation behaviours impacted the infant’s gastric emptying and the rate of protein hydrolysis. These results provide useful information for developing and designing healthier infant formulae by allowing greater control over the manipulation of protein bioavailability.
Figures 2.1 & 2.3 are re-used with permission. Figure 2.2 (from Bourlieu et al., Specificity of infant digestive conditions: some clues for developing relevant in vitro models, Critical Reviews in Food Science and Nutrition, 54(11), 1427-1457 Figure 1) is © 2014 Informa UK Limited, trading as Taylor & Francis Group, and reprinted by permission.
Keywords: 300607 Food technology